Non-muscle myosin IIC predominantly expressed in the slow-twitch skeletal muscles impedes age-related muscle weakness - Hiroki Hamaguchi; Shino Hiraoka; Kun Tang; Haonan Zhu; Yoshitaka Mita; Yasuro Furuichi; Nobuharu L. Fujii; Yasuko Manabe (PLoS ONE, 2025)
Skeletal muscle expresses three types of non-muscle myosin (NM) II in addition to skeletal type myosin. While immature myoblasts have been reported to express NMIIA and NMIIB, playing roles in cell morphology, the specific localization and function of NMIIC in skeletal muscle cells remain unclear. In this study, we aimed to investigate the expression pattern and the physiological role of NMIIC in skeletal muscle. NMIIC was specifically expressed in the slow-twitch muscles such as soleus, which primarily consists of type I and type IIa fibers, and its expression increased as muscle differentiation progressed. To explore the function of NMIIC in skeletal muscle, we used whole-body NMIIC knockout (KO) mice. Myofiber size was slightly but significantly decreased in the soleus of young (18–20-week-old) NMIIC KO mice. However, contractile force of the isolated soleus muscle in the NMIIC KO mice did not differ from that of wild-type mice, suggesting that the slight reduction in fiber size has limited physiological significance at this age. Interestingly, in 81-week-old NMIIC KO mice, soleus contractile force was significantly reduced despite no difference in fiber size between aged wild-type and NMIIC KO mice. Notably, NMIIC expression levels were higher in aged than young mice. These findings suggest that while NMIIC has minimal impact on skeletal muscle function under young and healthy conditions, it may play a crucial role in maintaining muscle function when muscle is compromised at age.